Neonatal amygdala microstructure mediates the relationship between gestational glycemia and offspring adiposity - Kok Hian Tan; Fabian Yap; Yap-Seng Chong; Shirong Cai; Peter D Gluckman; Izzuddin M Aris; Wen Lun Yuan; Keith M Godfrey; Lynette Pei-Chi Shek; Marielle V Fortier; Michael J Meaney; Yung Seng Lee; et al. (BMJ Open Diabetes Research & Care)
Introduction To determine if variations in the neonatal amygdala mediate the association between maternal antenatal glycemia and offspring adiposity in early childhood.Research design and methods 123 non-obese pregnant women with no pregnancy complications aside from gestational diabetes underwent a 75 g 2-hour oral glucose tolerance test at 26–28 weeks’ gestation. Volume and fractional anisotropy (FA) of the neonatal amygdala (5–17 days old) were measured by MRI. The Body Mass Index (BMI) z-scores and sum of skinfold thickness (subscapular and triceps) of these children were tracked up to 60 months of age (18, 24, 36, 48, 54 and 60 months).Results Maternal fasting glucose levels were positively associated with the offspring’s sum of skinfold thickness at age 48 months (β=3.12, 95% CI 0.18 to 6.06 mm) and 60 months (β=4.14, 95% CI 0.46 to 7.82 mm) and BMI z-scores at 48 months (β=0.94, 95% CI 0.03 to 1.85), 54 months (β=0.74, 95% CI 0.12 to 1.36) and 60 months (β=0.74, 95% CI 0.08 to 1.39). Maternal fasting glucose was negatively associated with the offspring’s FA of the right amygdala (β=−0.019, 95% CI −0.036 to −0.003). Right amygdala FA was negatively associated with the sum of skinfold thickness in the offspring at age 48 months (β=−56.95, 95% CI −98.43 to −15.47 mm), 54 months (β=−46.18, 95% CI −88.57 to −3.78 mm), and 60 months (β=−53.69, 95% CI −105.74 to −1.64 mm). The effect sizes mediated by right amygdala FA between fasting glucose and sum of skinfolds were estimated at β=5.14 (95% CI 0.74 to 9.53) mm (p=0.022), β=4.40 (95% CI 0.08 to 8.72) (p=0.049) mm and β=4.56 (95% CI −0.17 to 9.29) mm (p=0.059) at 48, 54 and 60 months, respectively.Conclusions In the offspring of non-obese mothers, gestational fasting glucose concentration is negatively associated with neonatal right amygdala FA and positively associated with childhood adiposity. Neonatal right amygdala FA may be a potential mediator between maternal glycemia and childhood adiposity.